Mentor-Mentee Relationship and Ethics - Karagözoğlu, Ahmet Alper; Özan, Mukadder Boydak; Ozdemır, Tuncay Yavuz (My University, 2024)
This study aimed to examine the mentor’s attitudes and behaviors in term of ethics in the relationship between mentor and mentee through mentee’s perspective. The participants consisted of six doctorate students enrolled at the Institute of Educational Sciences or the Institute of Social Sciences. The criterion sampling method was used for participant selection. Semi-structured interview form was used to collect data and thematic analysis method was performed in data analysis. According to the findings, the participants stated the importance of autonomy, guidance, time allocation, sharing knowledge and experience, being fair, and confidentiality in the relationship with their mentors. Also, it was revealed that the relationship between mentor and mentee is very important for career development and mentor is an important role-model. Another critical finding is that negative issues (i.e., mentor may not perform roles) are ignored since the mentee prefers to complete the process. It is concluded that ethical factors should be taken into account in the mentor-mentee relationship. This may solve the issues between mentor and mentee and prevent more complicated issues to arise.
Keywords: Ethics; Mentor and mentee relation; doctorate education